The diffusion of international norms of banknote iconography: A case study of the New Taiwan Dollar. (March 2017) - Hymans, Jacques E.C.; Fu, Ronan Tse-min
Abstract: There has been a dramatic rise in progressive values imagery on the banknotes of industrialized states over the past few decades. We see this trend as an instance of international norm diffusion and point to two causal mechanisms that have facilitated it: mimesis and professionalism. We hypothesize that national politicians are more subject to the mimetic mechanism, whereas central bank bureaucrats are more subject to the professionalism mechanism. We then probe the value of our theoretical contentions with a case study of the banknotes of the Republic of China, i.e. Taiwan. Using qualitative and quantitative content analysis, we show the convergence of the New Taiwan Dollar with advanced country norms of progressive banknote iconography around the year 2000. Then, using historical process-tracing analysis, we show that this convergence was engineered by national politicians who wanted banknote reform for mimetic and domestic political reasons, and central bank bureaucrats who wanted banknote reform for professional reasons. In short, the changes to these important symbols of national identity were reflections of different state actors' thirst for international belonging. Highlights: Explains the international diffusion of progressive values imagery on national banknotes. Defines mimetic and professionalism-driven causal mechanisms of international iconographic diffusion. Rigorously measures the convergence of New Taiwan Dollar iconography with advanced country banknote models. The most complete historical account of the mid-late 1990s New Taiwan Dollar reform process.